THE EFFECT OF BUSINESS TURNOVER, LEVEL OF EDUCATION, AND ACCOUNTING TRAINING ON THE QUALITY OF ACCOUNTING INFORMATION IN MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) IN ASEMROWO SUB-DISTRICT, SURABAYA CITY - Soesanto, Soesanto (JEA17: Jurnal Ekonomi Akuntansi, 2023)
The quality of accounting information or a lack of understanding of accounting information is one of the factors that makes it difficult for UMKM to develop and even fail to close their businesses. This study aims to examine whether there is an effect of business turnover, education level, and accounting training on the quality of accounting information. In collecting data using a questionnaire. The regression model used in this study is a multiple linear regression model with the help of SPSS. The sampling method for the study used the purposive sampling method (random) which obtained as many as 53 owners/managers of UMKM in Asemrowo District, Surabaya City. The results showed that the variable level of accounting education and training had a significant and significant effect on the quality of accounting information on UMKM. While the turnover variable has no effect on the quality of accounting information on UMKM.